A 4-Year Audit of Open Method Chemoport Insertions through Cephalic Vein Performed In Hospital Tengku Ampuan Afzan - Sanjay, DS; Lee, KY; Syafiq, H; Salleh, MS (IIUM Medical Journal Malaysia, 2019)
Introduction: Many cancer patients in general require long term venous access such as chemoport for chemotherapy, as well as infusion of fluids and blood taking. However, chemoport insertions carry complications such as infection, blockage, pneumothorax and malposition. We received feedbacks regarding complications endured by patients after chemoport insertion from the respective teams managing the patients in our hospital. In view of that, we conducted a retrospective audit on the chemoport insertions which we have done. Materials and Methods: We conducted a retrospective audit on the chemoport insertions which was planned for open method insertion through cephalic vein performed over the last 4 years from 2014 to 2017. Results: A total of 102 chemoports were inserted. Majority of patient’s ages are 50-59 years old. 88 (86%) of the cases were done via open method whereas another 14 cases were converted to percutaneous route. Majority of patients (55%) of the patients have breast carcinoma followed by colorectal (28%), haematological (12%) and gynaecological malignancies (5%). Complications occurred in 10 patients (rate at 9.8%). Most common complications were catheter related infection (5 cases) followed by wound infection (3 cases) and malposition (2 cases). Malposition was detected on post-operative chest radiograph and revision was done. All catheter related infection occurred in patients with haematological malignancies. Our complication rate of 9.8% is lower than the accepted complication rate of 15-25% worldwide. Conclusion: Chemoport provides a robust vascular access especially for the purpose of chemotherapy infusion. We showed with adequate training and privileging, it can be performed with very limited complications.